A Survey on Security Threats and Countermeasures in Internet of Medical Things (IoMT). Issue 6 (23rd July 2020) - Papaioannou, Maria; Karageorgou, Marina; Mantas, Georgios; Sucasas, Victor; Essop, Ismael; Rodriguez, Jonathan; Lymberopoulos, Dimitrios
Abstract: Internet of medical things (IoMT) is an emerging technology aiming to improve the patient's quality of life by enabling personalized e‐health services without limitations on time and location. Nevertheless, IoMT devices (eg, medical sensors) that constitute the key underlying elements of the IoMT edge network are vulnerable to various types of security threats and thus, they pose a significant risk to patient's privacy and safety. Based on that and the fact that the security is a critical factor for the successful integration of IoMT technology into pervasive healthcare systems, there is an urgent need for novel security mechanisms to preserve the security of the IoMT edge network. Toward this direction, the first step is the comprehensive understanding of existing and potential threats to the IoMT edge network environment. Thus, in this article, we provide a categorization of security threats to the edge network environment based on the major security objectives that they target. Moreover, we present a categorization of security countermeasures, derived from the literature, against threats to IoMT edge networks. The authors' intent is to provide a foundation for organizing research efforts toward the development of proper security countermeasures for protecting IoMT edge networks against internal and external threats. Abstract : In this paper, we identify the security threats to which IoMT edge networks are exposed and provide a categorization of the identified threats based on the major security objectives that they target. Furthermore, a categorization of security countermeasures against threats to IoMT edge networks is presented. The authors' intent is to provide a foundation for organizing research efforts toward the development of proper security countermeasures for protecting IoMT edge networks from a wide range of internal and external security threats.